Legal and Fiscal Implications of Class C Mineral Tax on Geological Resource Management - Muh. Akbar Fhad Syahril; Nurhaedah Hasan; Haslinda Hasan (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines the management of Group C minerals, focusing on challenges such as illegal mining, inaccurate valuation of sale value, weak supervision, and the lack of integration of environmental and social aspects in mining regulations. Through the analysis of Law No. 4 of 2009 on Mineral and Coal Mining and case studies in several regions, this study suggests the revision of regulations, improvement of supervision, application of information technology, and cooperation between governments for more effective management. These recommendations aim to assist policymakers in reforming the mining sector, especially for Group C minerals, to ensure its management is more equitable, efficient, and sustainable, while emphasizing the importance of adaptive and flexible policies to face global dynamics.